Metabolomics analysis of five cultivars of Sorghum bicolor reveals the contribution of flavonoid pathway to tannin content - Xianlin Ni; Wenjing Long; Lijuan Gong; Jia Zheng; Yanghua Li; Zhenhui Kang (PLoS ONE, 2025)
This study aims to utilize metabolomics to elucidate the key metabolites and metabolic pathways contributing to the quality differences among the grains of ‘hongyingzi’ (hyz) sorghum and four other varieties naming ‘jinuoliang’ (Jinl), ‘jinnuoliang’ (Jinnl), ‘lunuohong’ (lnh) and ‘liaoza 19’ (lz19). By analyzing the metabolomics data of the five sorghum varieties, we identified a total of 384 differentially accumulated metabolites (DAMs). Among these, flavonoids, phenolic acids and lipid compounds were the most abundant, exhibiting varying degrees of upregulation and downregulation. Compared to the four cultivars, the hyz sorghum differently exhibited 78, 40, 59 and 63 flavonoids; 29, 54, 30 and 30 phenolic acids; and 9, 27, 26 and 20 lipids, respectively. Multiple comparisons among the five sorghum varieties also identified 38 common DAMs, and the flavonoid pathway is particularly significant in KEGG enrichment. Additionally, as a high tannin content variety, correlation analysis revealed in sorghum that ellagic acid-4-O-glucoside plays a central role in tannin synthesis. These findings would highlight significant differences in the metabolomic profiles between hyz and the control varieties, providing valuable insights for the exploration of key genes involved in flavonoid metabolism and biosynthesis pathways in sorghum seeds.